21 High-sensitivity cardiac troponin concentrations at presentation in patients with st-segment elevation myocardial infarction. (17th July 2020) - Wereski, Ryan; Lee, Ken K; Smith, Stephen W; Chapman, Andrew R; Lowe, David J; Gray, Alasdair; Mills, Nicholas L
Abstract : Background: The widespread adoption of high-sensitivity cardiac troponin testing has encouraged the use of pathways to accelerate the rule-out and rule-in myocardial infarction in the Emergency Department. These pathways are not recommended for patients with ST-segment elevation, but there is a risk they may be applied incorrectly given that interpretation of the electrocardiogram is subjective, dependent on experience, and signs may be masked in those with posterior myocardial infarction. Methods: Consecutive patients with suspected acute coronary syndrome were enrolled in a stepped-wedge cluster randomized controlled trial across ten hospitals in Scotland. The index diagnosis was adjudicated two clinicians independently in all patients with high-sensitivity cardiac troponin I concentrations above the sex-specific 99th centile on serial testing and abnormalities on the electrocardiogram recorded. The proportion of patients with ST-segment elevation myocardial infarction and concentrations below the rule-out threshold (<5 ng/L), 99th centile (<16 ng/L and <34 ng/L for women and men) and rule-in threshold (<52 ng/L) at presentation were determined. Secondary analysis determined the effect of symptom duration, and culprit vessel location, on troponin concentrations. Results: In total, we enrolled 48, 282 consecutive patients with suspected myocardial infarction were enrolled, with 925 having an index diagnosis of STEMI. The majority (83.5%, 772/925) of patients had a troponin concentration above the 99th-centile on presentation. The median troponin concentration on presentation was 196 ng/L [46.0, 21611.], with 2.2% (20/925) and 14.4% (133/925) under the 5ng/L rule-out threshold, and <99th-centile respectively. Relying on a rule-in threshold of 52ng/L would miss more than 1 in 4 patients (26.8%, 248/925) with STEMI. Patients presenting soon after symptom onset had significantly lower troponin concentrations (<2 hours, median 96.0ng/L [26.0, 494.0] vs ≥2 hours, median 294.ng/L [59.0, 3042.0], p<0.001). Discussion: In patients with suspected acute coronary syndrome who have a final diagnosis of ST-segment elevation myocardial infarction, high-sensitivity cardiac troponin concentrations are below the rule-out and rule-in threshold at presentation in more than 1 in 50 and 1 in 4 patients, respectively. Clinicians should not rely on cardiac troponin concentrations to guide initial treatment decisions in patients with possible ST-segment elevation myocardial infarction. Conflict of Interest: None